Implementasi Metode VIKOR Untuk Menentukan Bahan Kulit Terbaik Dalam Pembuatan Ikat Pinggang - Maringan Sianturi; Sri Wulan; Suginam Suginam; Rohminatin Rohminatin; Mesran Mesran (Universitas Budi Darma, 2018)
The belt is a complement of clothing made of leather or hard clothing that serves to tie a pair of pants or skirts around the waist. Belts are part of fashion. There are several types of belts, which are divided into models, materials, sizes, and so on. For example, police belt, security guard belt, TNI belt and others. Generally, the parts of the belt (belt construction) are divided into two parts, namely Traps and Buckle. The traps are usually made of leather, while the buckle is usually made of metal, Decision Support System (DSS) is a computerized system designed to improve the effectiveness of decision making to solve problems which are semi-structured and unstructured so that in the process of making decisions that can be done more quality.Â